Pengaruh Current Ratio, Return on Asset, dan Net Profit Margin terhadap Debt to Equity Ratio pada PT Unilever Indonesia Tbk Periode 2015-2024 - Lestari, Putu Ita; Purnamayasa, I Komang Widya (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study examines the role of liquidity and profitability in shaping the capital structure of PT Unilever Indonesia Tbk over the 2015–2024 period. Using 40 quarterly observations derived from published financial statements, this research applies multiple linear regression to analyze the effect of Current Ratio (CR), Return on Assets (ROA), and Net Profit Margin (NPM) on the Debt to Equity Ratio (DER). The results indicate that CR has a significant negative effect on DER, suggesting that stronger liquidity reduces reliance on debt financing. NPM also shows a significant negative influence on DER, highlighting the importance of operational profitability in strengthening internal funding capacity. In contrast, ROA does not exhibit a significant effect on DER, implying that asset-based profitability does not necessarily translate into lower leverage decisions. Simultaneously, CR, ROA, and NPM explain a substantial proportion of the variation in DER. These findings contribute to capital structure theory by demonstrating that liquidity and operational profitability play a more decisive role than asset efficiency in determining leverage, particularly in mature consumer goods firms facing extreme leverage trends in recent periods.